Mudanças no rural nordestino: uma análise dos determinantes da pluriatividade nas famílias rurais nordestinas, no ano de 2011 - Cruz, Monica Soares (2013)
This study aims to the evaluate the determinants for rural households northeastern be pluriactive, in 2011. For this, at first, we conducted a review of national and international literature in order to get beyond the theoretical part which refers to the study of pluriactivity identify possible determinants of the phenomenon. In this rescue, it was the observed determinants could be macroeconomic in nature and / or microeconomics. Therefore, it became necessary to describe the characteristics of the region under study, the Northeast. In order to identify the determinants were two estimated Probit models, one based on the literature review and the second with a variable characteristic of the Northeast, the transfers. For this, we used the PNAD in 2011. The results indicate both the microeconomic determinants are : gender, race, age, years of education, hours worked, number of family members, per capita income, transfer the macroeconomic in nature: living conditions (water, energy, sanitation ), housing location. In addition to identifying the determinants, the Econometric model allows to know the probability of each variable on the dependent variable, which stood out: the transfer variable, gender, per capita income, number of family members, housing conditions and housing location. Therefore, it is concluded that it is the set of determinants (macro and micro) allow rural families become northeastern pluriactive. However, one can not fail to consider may also have other determinants were not captured due to the availability of data, which may be indications for future studies. In summary, the pluriactivity in the Brazilian Northeast is a phenomenon distinct from found in Europe and southern Brazil. It is a pluriactivity survival that is part of the strategies of rural households in the Northeast to ensure their social reproduction amid the poverty of the region